Methodological quality of guidelines in gastroenterology - Malheiro, Rui; de Monteiro-Soares, Matilde; Hassan, Cesare; Dinis-Ribeiro, Mário (Endoscopy, 2014)
Background and study aims: Clinical guidelines are a common feature in modern endoscopy practice and they are being produced faster than ever. However, their methodological quality is rarely assessed. This study evaluated the methodological quality of current clinical guidelines in the field of gastroenterology, with an emphasis on endoscopy.Materials and methods: Practice guidelines published by the American College of Gastroenterology (ACG), American Gastroenterological Association (AGA), American Society for Gastrointestinal Endoscopy (ASGE), European Society of Gastrointestinal Endoscopy (ESGE), British Society of Gastroenterology (BSG), National Institute for Health and Care Excellence (NICE), and the Scottish Intercollegiate Guidelines Network (SIGN) were searched between September and October 2012 and evaluated using the AGREE II (Appraisal of Guidelines for Research and Evaluation) instrument (23 items, scores 1 – 7 for each item; higher scores mean better quality).Results: A total of 100 guidelines were assessed. The mean number of items scoring 6 or 7 per guideline was 9.2 (out of 23 items). Overall, 99 % of guidelines failed to include the target population in the development process, and 96 % did not report facilitators and barriers to guideline application. In addition, 86 % did not include advice or tools, and 94 % did not present monitoring or auditing criteria.Conclusion: The global methodological quality of clinical guidelines in the field of gastroenterology is poor, particularly regarding involvement of the target population in the development of guidelines and in the provision of clear suggestions to practitioners.